(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kovchin N. A. Didactic and psychological aspects of the development of cognitive abilities of schoolchildren in learning geography. This article analyzes the possibilities of development opportunities and school context for their intellectual adaptation in the modern world in the learning process. Disclosed the content of the textbook development factor, filed substantial characteristic of structuring principles of didactic material on geography.